In the kitchen - Greenburg, J. C. (Judith C.); Palen, Debbie (New York Random House, 2002)
After being shrunk by a shrinking machine, Alexander, his cousin Judy, and Thudd the robot encounter drain flies, a cockroach, and worse as they work their way through Mrs. Scuttle's house toward safety.
"A stepping stone book."
Keywords: Inventions -- Fiction; Size -- Fiction; Insects -- Fiction; Cousins -- Fiction